Design and test of soft-pot-tray automatic embedding system for light-economical pot seedling nursery machine - Chen, Lintao; Ma, Xu; Wang, Cong; Li, Hongwei; Li, Zehua; Chen, Xueshen; Chen, Tao (International Journal of Agricultural and Biological Engineering, 2020)
Most of the commercially-available pot seedling nursery machines are incompatible with soft-pot-trays and are labor-intensive and low in productivity. A soft-pot-tray automatic embedding system was developed in this study to achieve automatic embedding of the soft pot tray into the hard tray following sowing and covering with soil. A control system was constructed using the Arduino program development environment. An embedded-hard-tray automatic lowering mechanism and conveyor-belt-based pot-tray embedding system were designed. Dynamics analysis was conducted to derive an equation to describe the embedding process of the soft pot tray into the embedded hard tray. A prototype of the soft-pot-tray automatic embedding system was manufactured and tested. The analytical equation suggested that a minimum linear velocity of 0.86 m/s was required for a complete embedding process. The experimental results showed that the embedded-hard-tray automatic lowering mechanism was reliable and stable as the tray placement success rate was greater than 99%. The successful tray embedding rate was 100% and the seed exposure rate was less than 1% with a linear velocity of the conveyor belt of 0.92 m/s. The experiment findings agreed well with the analytical results. The proposed soft-pot-tray automatic embedding system satisfied the technical specifications for a light-economical pot seedling nursery machine. Keywords: automatic embedding, pot seedling nursery machine, embedded hard tray, soft pot tray, conveyor-belt embedding system DOI: 10.25165/j.ijabe.20201301.4726 Citation: Chen L T, Ma X, Wang C, Li H W, Li Z H, Chen X S, et al. Design and test of soft-pot-tray automatic embedding system for light-economical pot seedling nursery machine. Int J Agric & Biol Eng, 2020; 13(1): 91–100.